PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 009 KERAMPAL KECAMATAN BATANG GANSAL - ', Tiurlina; Noviana, Eddy; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes IPA class IV SDN 009 Kerampal Kecamatan Batang Gansal by implementing cooperative learning model NHT. Subjects in this study is a fifth grade students enrolled in the second semester of the 2015/2016 TP totaled 17 students consisting of 11 boys and 7 girls. This type of research is a classroom action research (Classroom Actions Research) which comprises two cycles (4 meetings). Based on the research and analysis of the data found that the average value before implementation of cooperative learning model NHT is 60.58. In the first cycle UH 1 daily value increased to 68.74 students who have increased as much as 13.46%, with the number of students who completed 11 students (64.71%). In the second cycle increased learning outcomes as much as 18,82% to 81.68. All students completed the implementation of the UH 2 as many as 17 people (100%). Activities teachers in the first cycle and the second cycle of successes 70.83% with good criterion. At the 2nd meeting becoming a 79.17% with good criterion. In the second cycle to meeting all first gained 83.33% success criteria very well. At the 2nd meeting be 95.83% with qualifications were excellent. Activities of students in the first cycle-one meetings to acquire 66.67% with good success. At the meeting of 2 to 75% with good criterion. In the second cycle to meeting all first gained success 83.33% with good criterion. At the 2nd meeting increased to 87.5% with qualifications also good. Based on the results of this study concluded that the implementation of cooperative learning model NHT can improve learning outcomes IPA class IV SDN 009 Kerampal Kecamatan Batang GansalÂ Keywords: NHT Model Cooperative Learning and Learning Outcomes IPA